Are Managers More Machiavellian Than Other Employees? - Mehrzad B. Baktash; Uwe Jirjahn (Global Labor Organization (GLO), 2023)
Concerns about corporate scandals and abusive leadership suggest that individuals with an opportunistic and manipulative personality take advantage of incomplete incentive and control systems to get their way into managerial positions. Against this background, we examine whether there is an association between Machiavellianism and occupying a managerial position. We suggest how to incorporate the psychological concept of Machiavellianism into agency theory and hypothesize that individuals scoring high on Machiavellianism are more likely to attain and keep a managerial position. Using a large and representative panel dataset from Germany, our empirical analysis confirms a strong and positive relationship between Machiavellianism and occupying a managerial position. This result holds in various robustness checks and in instrumental variable estimations accounting for possible endogeneity. Furthermore, our analysis provides evidence that the relationship is monotone; i.e., those with the highest scores of Machiavellianism are most likely to be managers. It also suggests that the direction of influence runs from Machiavellianism to occupational status and not vice versa.
Keywords: D23; D90; J24; M12; M51; 330; Machiavellianism; Dark Triad; Managers; Agency Theory; Occupational Sorting